Production performance of lettuce (Lactuca sativa): aquaponics versus traditional soil - Rana, KM Shakil; Jahan, Mymona; Ferdous, Zannatul; Salam, MA (Asian Journal of Medical and Biological Research, 2018)
Feeding the ever increasing population in a safe way has become a rising challenge because of reckless use of natural resources. Substitution of traditional farming system with cost effective integration of different production units has emerged as potential solution. In this regards, aquaponics has already put back the traditional farming systems in facing the burning issues of food safety. The experiment was designed to make a comparison of lettuce (Lactuca sativa) production between aquaponics (T1) and traditional soil growbeds (T2) in laboratory condition at the Aquaponics Laboratory, Bangladesh Agricultural University (BAU), Mymensingh. Each of the treatment has three replications that were placed randomly. A Seven hundred fifty liter water tank was set for fish rearing where 50 tilapia (Oreochromis niloticus) and 20 magur (Clarias batrachus) fry were released. Tilapia was fed with commercial floating feed while magur with sinking feed. Six (44×26×24 cm3) containers, three for each treatment, were used for lettuce sapling plantation. The fish waste water was irrigated into aquaponics beds and then returned to the fish tank as the thumb role of aquaponics. Fish, plants, water and soil quality parameters were sampled fortnightly, analyzed chemically in the aquaponic laboratory. The results revealed that the performance of T2was better than the T1 in terms of lettuce growth in respect of plant height, leaf number, plant and root weight. Lettuce production was comparatively higher in T2 (123.25 tons/ha/89 days), than T1 (107.89 tons/ha/89 days). This might be attributed to the higher nutrient content of the traditional soil (T2). At The end of the experiment, the survival rates were 96 and 80% for tilapia and magur respectively whereas the total productions were 47.33 and 4.19 tons/ha/105days respectively. Further research needed to ascertain the superiority of these systems in food production. Asian J. Med. Biol. Res. June 2018, 4(2): 149-156